(untitled) (Psychology Travelogs, 2023)
The article presents a theoretical and empirical analysis of the influence of anxiety on the peculiarities of the professional activity of flight attendants. The relevance of the research is substantiated and it is stated that the study of this problem is an important scientific task, since in Ukraine today the airspace for civil aviation remains closed for an indefinite period, which in turn creates anxiety and uncertainty among flight attendants. Summarizing the views of various researchers, it is proved that, on the one hand, anxiety is considered as a subjective discomfort of the individual, which negatively affects her interaction with others and her attitude towards himself; on the other hand, anxiety also has a positive function that is associated with mobilization of a person in certain situations. A theoretical analysis of scientific research was carried out regarding the impact of anxiety on the peculiarities of professional activity. The place and its influence on the work of the flight attendants have been determined. The results of an empirical study are presented. Characteristic symptoms of anxiety, which directly affect the characteristics of the professional activity of flight attendants, are outlined and indicated: rapid heartbeat, decreased level of concentration, feeling of danger, uncontrollable emotions, high level of conflict, decreased self-confidence, irritability, restlessness, headache, aggressiveness. It is noted that anxiety negatively affects the professional activity of flight attendants. The professional activity of a flight attendant requires them to be collected, clear, responsible, organized, have a high level of concentration, stress resistance, sociability, the ability to find an approach to a person and the ability to provide first aid. In the context of our study, anxiety is considered as something that can significantly affect the efficiency of professional activity and can prevent flight attendants from fully performing their professional activities and solving certain important tasks.